Differential efficacy of three cycles of CMF followed by tamoxifen in patients with ER-positive and ER-negative tumors: Long-term follow up on IBCSG Trial IX - Aebi, S. (Oxford University Press, 2011)
Background: The benefit of adjuvant chemotherapy in postmenopausal patients with estrogen receptor (ER)-positive lymph node-negative breast cancer is being reassessed. Patients and methods: After stratification by ER status, 1669 postmenopausal patients with operable lymph node-negative breast cancer were randomly assigned to three 28-day courses of ‘classical’ CMF (cyclophosphamide, methotrexate, 5-fluorouracil) chemotherapy followed by tamoxifen for 57 months (CMF→tamoxifen) or to tamoxifen alone for 5 years. Results: ERs were positive in 81% of tumors. At a median follow-up of 13.1 years, patients with ER-positive breast cancers did not benefit from CMF [13-year disease-free survival (DFS) 64% CMF→tamoxifen, 66% tamoxifen; P = 0.99], whereas CMF substantially improved the prognosis of patients with ER-negative breast cancer (13-year DFS 73% versus 57%, P = 0.001). Similarly, breast cancer-free interval (BCFI) was identical in the ER-positive cohort but significantly improved by chemotherapy in the ER-negative cohort (13-year BCFI 80% versus 63%, P = 0.001). CMF had no influence on second nonbreast malignancies or deaths from other causes. Conclusion: CMF is not beneficial in postmenopausal patients with node-negative ER-positive breast cancer but is highly effective within the ER-negative cohort. In the future, other markers of chemotherapy response may define a subset of patients with ER-positive tumors who may benefit from adjuvant chemotherapy.